GENERIC STRATEGY STUDY IN HOTEL DESIGN IN THE NEW NORMAL ERA. CASE STUDY: URBAN INDEPENDENT HOTEL - Tecky Hendrarto; Ratu Sonya Mentari Haerdy; Asep Yudi Permana; Nyi Raden A Putri Anggiandari (Program Studi Arsitektur S-2 Universitas Pendidikan Indonesia, 2022)
The new normal era has had an impact on the decline of the economy and tourism in the city of Bandung. This condition has an impact on the regional income of the City of Bandung due to restrictions on foreign and domestic tourists. The decline in hotel occupancy is due to the lack of tourist visits. Hoteliers experience difficulties in maintaining their business due to the lack of discussion on this matter. Therefore, the designer's perspective can be a reference for managers and decision-makers to develop the hotel business efficiently during a pandemic. This study uses a descriptive analysis method from Hotel Urban Merdeka as a case study, which was able to survive during a pandemic. This research shows that generic strategies in hotel design are very important to attract and retain customers in the new normal era. Therefore, it is important for hotel owners to consider generic strategies, such as low cost, differentiation, and focus on certain market segments. Hotels that are responsive to changing trends and consumer preferences will be more successful in the new normal era. Factors such as hygiene, health, and safety are factors that must be considered. Different design concepts, such as eco-friendly designs or designs with artistic and cultural concepts added value to hotels and attract consumers' attention. The implication of this research is that hotel owners must consider generic strategies in their hotel designs and always be responsive to changing trends and consumer preferences. In addition, different design concepts must also be considered to provide added value to hotels and attract consumers' attention. Keywords: Tourism, repositioning, construction scenario, low cost